Multi cases optimal reactive power dispatch using evolutionary programming - Rahmatul Hidayah Salimin; Ismail Musirin; Zulkiffli Abdul Hamid; Afdallyna Fathiyah Harun; Saiful Izwan Suliman; Hadi Suyono; Rini Hasanah (Institute of Advanced Engineering and Science, 2020)
Evolutionary Programming (EP) is one of many types in Evolutionary Computation (EC) that used for optimization process. EP technique is used to find the optimal reactive power dispatch (ORPD) since it is one of the accessible options schemes that can be used on the system as a reactive power support. Sometimes, it is not necessary to operate all generators in order to perform ORPD to in achieve the objectives. Also, increment of reactive power load to the system will cause voltage decomposes with the increase in transmission loss in the system. Therefore, the proposed method decides the best grouping of generators that should be operated in system by bearing in mind the transmission loss reduction. ORPD will be used to minimize the transmission loss as well the increasing reactive power loading. This method conducted on IEEE 30-bus Test System with multi cases scenario. The best combination of operating generators determined and the transmission loss after optimization is smaller compared to the transmission loss before optimization resulted.